2021
DOI: 10.1016/j.heliyon.2021.e06944
|View full text |Cite
|
Sign up to set email alerts
|

Rapid automatized naming skills of children with intellectual disability

Abstract: Background: A deficit in Rapid Automatized Naming (RAN), acknowledged to be linked to dyslexia, has rarely been investigated as a potential explanation of the reading difficulties that children with intellectual disability (ID) often face. The existing studies mainly focused on adolescent or adults with ID matched to typically developing (TD) children on verbal mental age, or used a single RAN task. Aims: The aim of this study was to compare the RAN pattern and skills of children with ID and low reading skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…The purpose of the present study was to investigate the effects of adaptations of a phonics-based instructional reading program on word reading and spelling skills of individuals with ID who are AAC users. The instructional reading program (De Chambrier et al, 2021) that was adapted in the present study is designed to teach Frenchspeaking students with ID to read and spell. In a randomized controlled study, this program was shown to have a positive effect on word and non-word reading skills of verbal students with ID as well as a marginally significant positive effect with a medium effect size on spelling skills (Sermier Dessemontet et al, 2021).…”
Section: Open Access Edited Bymentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of the present study was to investigate the effects of adaptations of a phonics-based instructional reading program on word reading and spelling skills of individuals with ID who are AAC users. The instructional reading program (De Chambrier et al, 2021) that was adapted in the present study is designed to teach Frenchspeaking students with ID to read and spell. In a randomized controlled study, this program was shown to have a positive effect on word and non-word reading skills of verbal students with ID as well as a marginally significant positive effect with a medium effect size on spelling skills (Sermier Dessemontet et al, 2021).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…Reading and spelling lessons from an instructional reading program (De Chambrier et al, 2021) that were adapted to the needs of students who are AAC users were used in this study. The instructional reading program has been developed for Frenchspeaking students with ID.…”
Section: Literacy Programmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism underlying the RAN-reading relation is still a subject of debate. According to the double-deficit hypothesis, PA and RAN are two separable sources of reading dysfunction [24]. Some authors (e.g., [15,[25][26][27][28]) indicate that PA is an area of weakness in children with ID of different etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…Disability constitutes one of the greatest barriers for learning. Research has shown that students with intellectual disability (ID) have lower proficiency in reading compared to typical children (Dessemontet et al, 2017;van Wingerden et al, 2017;de Chambrier et al, 2021). To overcome these barriers, students with ID need highquality instruction.…”
Section: Introductionmentioning
confidence: 99%